Bt cotton and ecosystem impacts of pesticide reductions - Prakashan Chellatan Veettil; Vijesh V. Krishna; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
This paper examines the ecosystem impacts of transgenic Bt cotton technology resulting from reduced chemical pesticide use. Employing unique panel data from smallholder farmers in central and southern India, negative environmental and health effects of pesticide use are quantified with the environmental impact quotient (EIQ), with and without Bt technology. An environmentally-sensitive production function is estimated, treating the environmental risk of pesticide toxicity as an undesirable output in the production process. Negative externalities are significantly lower in Bt than in conventional cotton. The reduction in EIQ through Bt adoption has increased from 39% during 2002-2004 to 68% during 2006-2008. Bt adoption also contributes to higher environmental efficiency. We find that environmental efficiency is influenced by the quality of Bt technology; high-quality Bt seeds are associated with higher environmental efficiency than lower-quality seeds.
Keywords: D62; O44; Q12; Q16; 330; Bt cotton; Directional distance function; Environmental impact quotient; India; Pesticide externality